PHOTOACOUSTIC IMAGING SYSTEM FOR BIOLOGICAL TISSUES CHARACTERIZATION - Hui, Ling Chua; Huong, Audrey (Science & Engineering Research Support Society (SERSC), 2020)
The aim of this work is primarily to present the use of an in-house assembled photoacoustic (PA) system as an alternative means of biological tissues characterization to replace the use of conventional imaging modalities. PA imaging is able to provide illumination of biological tissues with strong optical absorption contrast and high spatial resolution at a short scanning time. The resulting acoustic signal detected by a transducer was used to determine the amplitude of tissues optical absorption via the measured phase value (Ф). This research investigated differences in PA response of different parts of chicken poultry namely fat, liver and muscle of different sizes. This work reported a consistent increase in the PA signals of all tissues with the sample size. While fat tissues were found to produce the largest PA signals with mean ± standard deviation (SD) of Ф = 1.12 ± 0.11, muscle produced the least signals with Ф = 0.828 ± 0.20. This work attributes this observation to the differences in the biophysical properties of these samples. This work concluded that this technology may be suitable used in the design and implementation of a handheld medical imaging device in the future.